Educational Transformation in the Global South and Europe: Comparative Perspectives on Policy and Innovation - Omar Abdel Rahman Rasyid (PT. Islamic Research Publisher, 2024)
Educational transformation has become a central agenda in many countries as they respond to rapid technological change, globalization, and shifting socio-economic demands. However, the trajectory and policy orientation of educational reform often differ significantly between regions. This study aims to analyze and compare the dynamics of educational transformation in the Global South and Europe, with a particular focus on policy frameworks and innovation strategies that shape contemporary education systems. By examining these comparative perspectives, the research seeks to identify patterns, challenges, and opportunities that influence the direction of educational reform across different socio-political contexts. This study employs a qualitative comparative research design using a systematic literature review approach. Academic articles, policy reports, and scholarly publications indexed in major international databases were analyzed to explore key themes related to educational policy reform, institutional innovation, governance models, and the integration of technology in education. The analysis was conducted through thematic coding and comparative synthesis to identify similarities and divergences between educational transformation strategies in the Global South and European countries. The findings reveal that educational transformation in the Global South is largely driven by efforts to expand access, improve institutional capacity, and address structural inequalities, often supported by international cooperation and development-oriented policies. In contrast, European education systems tend to emphasize innovation-driven reforms, including digital learning ecosystems, research-based policy development, and collaborative governance among educational stakeholders. Despite these differences, both regions increasingly prioritize curriculum modernization, digital transformation, and inclusive education as key components of educational reform. This study contributes to the scholarly discourse on global education policy by offering a comparative framework that highlights how contextual factors—such as governance structures, economic capacity, and socio-cultural dynamics—shape educational transformation. The findings provide valuable insights for policymakers, educators, and researchers seeking to develop adaptive and context-sensitive strategies for sustainable educational innovation in diverse global settings.